Screening for Fabry Disease in Patients With Juvenile Systemic Lupus Erythematosus - Ertugrul KIYKIM; Sezgin ŞAHİN and Tanyel ZUBARIOĞLU and Kenan BARUT and Amra ADROVIC and Mehmet Şerif CANSEVER and Ayşe Çiğdem AKTUĞLU ZEYBEK and Özgür KASAPÇOPUR (Archives of Rheumatology, 2020)
Objectives: This study aims to determine the prevalence of Fabry disease (FD) among patients with juvenile systemic lupus erythematosus (SLE). Patients and methods: This cross-sectional study included 76 juvenile SLE patients (12 males; 64 females; mean age 16±3.3 years; range, 8 to 23.5 years) who were diagnosed according to 1997 update of the 1982 American College of Rheumatology revised criteria for classification of SLE. Since the majority of patients were female, alpha-galactosidase A gene was investigated for mutations resulting in FD. Lysosomal accumulation of globotriaosylsphingosine (lyso-Gb3) was further evaluated in mutation positive subjects by using dried blood spot testing. Results: Alpha-galactosidase A gene screening did not yield any positive mutation in our 74 subjects. However, a heterozygous p.D313Y mutation was found in two females. These subjects were further investigated for lyso-Gb3 levels in dried blood spot samples and the levels of lyso-Gb3 being normal lead to exclusion of FD in these two patients. Conclusion: We do not suggest routine screening of FD in patients with juvenile SLE; however, prospective studies with larger sample sizes are needed for further analysis.